Main reasons for honey bee colony mortality in Portugal. A snapshot of beekeepers' beliefs - Pires, S (2014)
To investigate claims of abnormally high honey bee colony mortality in Portugal during 2011, a survey was carried out via telephone interviews. It included 662 (≈ 4%) registered Portuguese beekeepers and followed the basic 'Coloss' questionnaire. Interviewees were selected accounting for total numbers of colonies and the geographical distribution of their apiaries across the country. The 'sampling grid' was set to 5 beekeepers per county, fully covering continental Portugal and jointly considering the autumn and winter periods. The overall annual colony mortality that beekeepers historically regard as 'natural' for their own apiaries is 9.7 ± 0.2 (mean ± standard error of the mean), not significantly deviating from the 10.8 ± 0.2 they consider 'normal' for the wider region where their apiaries are located. Over the combined autumn and winter seasons, the initial number of interviewees' productive colonies (99428) decreased 3.6% (i.e. 3591). Furthermore, if the comparison is made with the total number of productive colonies existing in early spring of the previous year (93841), an increase of 2.1% was observed in April 2011. Although incorporating a considerable commitment to colony splitting and swarm captures, this increase is still surprising given the outcome of a nation wide survey focused on Nosema ceranae (showing that 51% of the 277 sampled apiaries across the country were infected by this microsporidian). It also demonstrates that the media hype generated around 'unexplained high colony mortality' occurring in Portugal was clearly unwarranted. When beekeepers were individually asked to provide their views on the main causes for the colony mortalities observed, albeit the regional variations, Varroa destructor was flagged (by 25% of them) as the key problem they are faced with in terms of colony survival. 'Poor quality' queens (mentioned by 13%), colony starvation (indicated by 12%), colonies overwintering in 'weak conditions' (pointed out by 11%) and 'nosemosis' (suspected by 4%) are other considerable sources of problems encountered. Twenty seven percent of the participating beekeepers also additionally singly brought up an extra difficulty from a residual group of additional 'relevant challenges' posed by wasps, ants, chalkbrood, American foulbrood, bee-eaters, pesticide intoxications or thymol application induced accidents.